2021
DOI: 10.1093/jbcr/irab015
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Adult Burn Management in the United Kingdom: A Regional Center Experience

Abstract: In this study, the authors aim to quantify the impact of COVID-19 on burns provision at an adult regional burn centre. Two cohorts of patients were identified for comparison: one during the beginning of the COVID-19 lockdown in April 2020 and a comparator cohort in April 2019. There was a 30% decrease in the incidence of adult burns in 2020. The mean total body surface area (TBSA) was 1.8% and 4.3% in 2019 and 2020, respectively. Scald injuries were the commonest mechanism of burns in both cohorts. Depth of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…This study showed a decreased number of burn injury patients during the pandemic; this was similar to reports from other more economically developed countries, such as Canada, the US, and the UK [10] , [12] , [17] , [18] . In Toronto, Canada, there was a 33% decrease in burn injury admissions at a burn center during a 5-month period within the pandemic [10] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study showed a decreased number of burn injury patients during the pandemic; this was similar to reports from other more economically developed countries, such as Canada, the US, and the UK [10] , [12] , [17] , [18] . In Toronto, Canada, there was a 33% decrease in burn injury admissions at a burn center during a 5-month period within the pandemic [10] .…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, less patients during the pandemic suffered from intended burns (9 [4.4%] vs 584 [8.5%]), assault injuries (14 [6.9%] vs 718 [10.5%]), head and/or neck injuries (37 [18.2%] vs 1685 [24.6%]), and associated inhalation injuries (74 [36.5%] vs 2877 [42.0%]). Regarding the severity and outcomes of burn injuries, a slightly higher %TBSA of partial-thickness burns (4 [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] vs 3 [0–10] %TBSA), shorter LOS (3 [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] vs 5 [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] days), and lower in-hospital mortality (18 [8.9%] vs 817 [11.9%]) were seen in patients during pandemic compared to before the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies were published by other burn centres from economically developed countries, such as the UK, the US, Canada, and Japan [ 5 , 10 , 11 , 12 , 13 ]. D'Asta et al reported a decrease in adult burn patients by 60% during the lockdown, although the number of paediatric burn cases increased by 8% at the same time [11] .…”
Section: Discussionsupporting
confidence: 77%
“…A slight decrease of admitted burn patients by 5.8% was reported by Codner et al [12] . Further, a regional burn centre located in the UK reported a 30% decrease in adult burns during the COVID-19 pandemic [13] . On the other hand, a study from a US centre reported more frequent paediatric burns during the COVID-19 pandemic [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Although some burn units have reported their measures [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], there are no data on the impact of these with regard to treatment outcomes. Most of the data published in the literature thus far refer to epidemiological and demographic data in addition to injury and treatment characteristics of burn patients [ 8 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%